An Unsuspected Crisis: The Government of Rodrigo Carazo Odio and his Ambivalent Commitment to «Neoliberal» Reform (1978-1982). First Part - Marchena Sanabria, Jorge (2021)
This article analyzes the contradictory responses that the Carazo Odio administration tried to promote to mitigate the economic crisis of the early 1980s. The objective is to provide a partial reconstruction of the process: how the government defined the crisis or its misunderstanding of it, the insistence on the rhetoric of sovereignty in the face of external financial entities, problems of monetary liquidity, clashes between political factions, among others. It is an approach to the internal dynamics of Costa Rican politics, emphasizing its contradictions between democratization and secrecy. For the preparation of the text, documents from the National Archives from the period 1978-1982 were used, especially from the Presidency Series and Proceedings of the Governing Council.